Przedprojektowy etap wdrażania systemu budżetowania - Ossowski, Marek (The opening stage of implementing budgeting system, 2008)
The aim of the article is to present an opening stage of implementing budgeting system. The author identified three main aspects connected with the opening stage, which are: presentation of the expected results, recognition of the strategic aims, and qualification the risk of unsuccessful implementing.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 15, s. 353-360